Probing behavior of Neophilaenus campestris on various plant species. Issue 12 (9th October 2021) - Cornara, Daniele; Morente, Marina; Lago, Clara; Markheiser, Anna; Garzo, Elisa; Moreno, Aranzazu; Fereres, Alberto
Abstract: The recent history of Xylella fastidiosa Wells et al. introduction in Europe illustrates how the lack of knowledge about the bacterium‐vector‐host interactions hinders the application of effective containment strategies, with the bacterial spread that currently appears relentless. Vector behavior is a key component in plant pathogen transmission; therefore, detailed knowledge of vector probing behavior on various host plants would furnish useful data for containing the bacterium. Aiming at this goal, we carried out electrical penetration graph (EPG)‐assisted probing behavior observations of the spittlebug, Neophilaenus campestris (Fallen) (Hemiptera: Aphrophoridae), a candidate vector widespread in all the areas where X. fastidiosa is currently established. Spittlebug probing was first characterized on one of its preferred host plants, Bromus madritensis L. (Poaceae), over short (6 h) and long (16 h) time spans. Thereafter, we performed comparative observations of the spittlebug probing on B. madritensis, olive, and grapevine. Overall, the probing behavior of N. campestris, that is, the main characteristic waveforms, did not differ substantially from that of Philaenus spumarius (L.) (Hemiptera: Aphrophoridae); however, here we report and describe a new kind of xylem activity interruption, provisionally termed N2, not previously observed in P. spumarius . Considering the time spent in xylem ingestion as a percentage of the total probing time (host‐suitability indicator used for spittlebugs), grapevine and B. madritensis are the preferred hosts for N. campestris, with olive as the least suitable among the plants tested. Successful probes, that is, probes during which xylem ingestion occurred, on grapevine were 2.5× greater than olive. Therefore, our data on N. campestris probing behavior suggest that the spittlebug role in X. fastidiosa epidemiology in European vineyards should be given more attention. In the present manuscript, we also discuss the current difficulties in interpreting and analyzing the outcomes of EPG studies on spittlebugs. Abstract : A key component in pathogen transmission is vector feeding behavior. We describe the probing and feeding behavior of Neophilaenus campestris (Hemiptera: Aphrophoridae), a candidate vector of the bacterium Xylella fastidiosa, over short and long time spans and on various host plants, that is, bromus, olive, and grapevine. Our data coupled with previous field surveys suggest that N. campestris should be regarded as a potential vector of X. fastidiosa in European vineyards.